Factors influencing anxiety in preoperative patients at RSUD Lasinrang Kab. Pinrang - Sukri; Agustina; Bonggalola (Akupun Tour Publisher, 2022)
Background: Surgery as a potential or actual threat to someone that can produce psychological and physiological stress reactions. Anxiety is the most dominant psychological condition that occurs in preoperative patients which results in not carrying out or canceling the operation itself. Purpose: The purpose of this study was to determine the relationship between characteristics (Age, Education, Knowledge) with the level of anxiety in preoperative patients. Method: This research is a correlation analytic study with a cross sectional approach. The research population is all patients who will undergo surgery at Lasinrang General Hospital, Pinrang Regency. The sampling technique used accidental sampling as many as 73 respondents. Data collection using a questionnaire and data analysis methodsusing Chi-square with a significance level of 0.05. Result: The results showed that most of the respondents in the adolescent category were 31 respondents (42.5%), most of them had low education as many as 47 respondents (64.4%), and most of the respondents had sufficient knowledge as many as 50 respondents (68.5%). The results of the Chi-Square test showed that there is a relationship between education (p 0.001) and knowledge (p 0.001) with the level of anxiety of preoperative patients and there is no relationship between age with preoperative anxiety level (p 0.618). Conclusion: There is a relationship between education and knowledge with preoperative anxiety levels at Lasinrang General Hospital, Pinrang Regency. The results of this study are expected to be used as input to improve nursing services, which in turn can reduce the level of anxiety of patients who will face surgery.